Algorithm of decoding of convolutional codes in communication links with multiplexing - M.U., Konyshev; A.V., Kozachok; A.V., Pankratov; K.E., Petrov (Journal of Science and Technology on Information security, 2020)
Abstract— The model of the discrete communication link with multiplexing considering Markov’s properties of the condensed sources of messages and a source of errors is considered. The algorithm of decoding of convolutional codes in communication links with multiplexing considering the statistical properties of a source of errors and an encoded flow received on the basis of recognition and the subsequent information analysis about the regular sequences in multiplex digital flows is offered. Methods of estimation of rows of distributions of two-dimensional random value in a flow of errors and an encoded flow are offered. Tóm tắt— Bài báo trình bày mô hình truyền thông rời rạc kết hợp ghép kênh có xem xét thuộc tính Markov của các nguồn thông báo và nguồn lỗi. Sau đó đề xuất thuật toán giải mã mã chập trong liên kết truyền thông với ghép kênh có tính đến các thuộc tính thống kê của nguồn lỗi và luồng mã hóa thu được trên cơ sở nhận biết và phân tích thông tin các chuỗi thông thường trong ghép kênh kỹ thuật số. Từ đó đưa ra được phương pháp ước tính các hàng của phân bố giá trị ngẫu nhiên hai chiều trong luồng lỗi và luồng mã hóa.